1989
DOI: 10.1152/jappl.1989.66.5.2239
|View full text |Cite
|
Sign up to set email alerts
|

Venous occlusion plethysmography reduces arterial diameter and flow velocity

Abstract: The measurement of peripheral blood flow by plethysmography assumes that the cuff pressure required for venous occlusion does not decrease arterial inflow. However, studies in five normal subjects suggested that calf blood flow measured with a plethysmograph was less than arterial inflow calculated from Doppler velocity measurements. We hypothesized that the pressure required for venous occlusion may have decreased arterial velocity. Further studies revealed that systolic diameter of the superficial femoral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 0 publications
4
45
1
Order By: Relevance
“…However, it is well documented that dynamic measurements using a strain gauge can be greatly affected by fluid shifts typical of working or exercising limbs (e.g., bone flow, interstitial fluids). 21,58 Such concerns are demonstrated clearly in this study by the large elevation of flow recorded by the strain gauge after the halt of exercise despite rapid local recovery of rBF, r _ VO 2 , THC, and StO 2 measured by DCS/NIRS. Also, the VO protocol with SGVP measurement cannot be done continuously during exercise.…”
Section: Hemodynamic Parametersmentioning
confidence: 60%
See 1 more Smart Citation
“…However, it is well documented that dynamic measurements using a strain gauge can be greatly affected by fluid shifts typical of working or exercising limbs (e.g., bone flow, interstitial fluids). 21,58 Such concerns are demonstrated clearly in this study by the large elevation of flow recorded by the strain gauge after the halt of exercise despite rapid local recovery of rBF, r _ VO 2 , THC, and StO 2 measured by DCS/NIRS. Also, the VO protocol with SGVP measurement cannot be done continuously during exercise.…”
Section: Hemodynamic Parametersmentioning
confidence: 60%
“…57 Many concerns have arisen over the viability of using SGVP to measure BF during or following dynamic exercise protocols. 41,58 SGVP measures the change in limb circumference and thereby calculates the rate of the change during VO as inflowing blood. SGVP assumes that circumference change is caused by BF.…”
Section: Hemodynamic Parametersmentioning
confidence: 99%
“…A 30% reduction in blood¯ow, measured by 133 Xenon clearance in the tibialis anterior, has been noted following venous occlusion at the thigh to 5.3 kPa (40 mmHg; Henriksen and Sjersen 1977), and this was attributed to a local veni-arteriolar re¯ex. Diameter and¯ow velocity also decreased in the femoral and popliteal arteries when a thigh cu was in¯ated to 5.3 kPa (Hiatt et al 1989), and Sundberg and Kaijser (1992) reported that external compression of the legs of healthy subjects by application of 6.7 kPa (50 mmHg) within a pressure chamber reduced leg blood¯ow by an average of 16% during submaximal cycle exercise. This indicates that a modest restriction to perfusion occurs with venous occlusion, and the results of the present study show that twitch contractions are sensitive to this.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the extent that the strain-gauge plethysmography approach reflects muscle blood flow during the actual performance of exercise has recently been questioned (4). The controversy is further supported by the results of earlier studies that clearly demonstrate that the occlusion pressure required for obtaining the measurement of blood flow using this technique causes a significant reduction in muscle blood flow (5,20).To circumvent the inherent limitations of other techniques, the use of Doppler ultrasound has been used to measure steady-state as well as transient changes in blood flow during exercise with high temporal resolution (18,22,39,48). However, to our knowledge, the application of Doppler techniques to investigate possible sex differences in muscle blood flow has only recently been examined in the leg (36).…”
mentioning
confidence: 98%
“…Therefore, the extent that the strain-gauge plethysmography approach reflects muscle blood flow during the actual performance of exercise has recently been questioned (4). The controversy is further supported by the results of earlier studies that clearly demonstrate that the occlusion pressure required for obtaining the measurement of blood flow using this technique causes a significant reduction in muscle blood flow (5,20).…”
mentioning
confidence: 99%